Security Management in Hybrid War With Special Reference to U.S. Management - Mirković, Vladan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Hybrid warfare captures the attention of professional and the general public, with in most cases the emphasis on the content of hybrid warfare. However, the success of hybrid warfare does not result from its content, but from the synergistic effect that arises from the successful integration of the activities of a large number of subjects into a single activity. The task of achieving such integration has the security management, which, acting on the basis of legal and political acts, sholud achieve organizational and functional unity of numerous and diverse entities in achieving the desired goal.